2013
DOI: 10.1136/gutjnl-2012-302090
|View full text |Cite
|
Sign up to set email alerts
|

Enteroglial-derived S100B protein integrates bacteria-induced Toll-like receptor signalling in human enteric glial cells

Abstract: Human EGC interact with bacteria and discriminate between pathogens and probiotics via a different TLR expression and NO production. In EGC, NO release is impaired in the presence of specific inhibitors of the TLR and S100B pathways, suggesting the presence of a novel common pathway involving both TLR stimulation and S100B protein upregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(191 citation statements)
references
References 45 publications
(64 reference statements)
9
179
2
1
Order By: Relevance
“…S100B targeting has already been tested in other disease models with promising results. In fact, pentamidine, a S100B inhibitor, reduces S100B and RAGE expression in an animal model of Alzheimer's disease, with consequent reduction of pro-inflammatory milieu in the hippocampus [68]. Other potential therapeutic strategies may be the use of specific RAGE antibodies to prevent S100B binding, small molecules or anti-S100B aptamers [69,70].…”
Section: Discussionmentioning
confidence: 98%
“…S100B targeting has already been tested in other disease models with promising results. In fact, pentamidine, a S100B inhibitor, reduces S100B and RAGE expression in an animal model of Alzheimer's disease, with consequent reduction of pro-inflammatory milieu in the hippocampus [68]. Other potential therapeutic strategies may be the use of specific RAGE antibodies to prevent S100B binding, small molecules or anti-S100B aptamers [69,70].…”
Section: Discussionmentioning
confidence: 98%
“…S100␤ is constitutively expressed by EGC and seems to play an important role in IBD. It has been demonstrated that immunostaining of s100 is increased in rectal specimen of patients suffering from UC compared with healthy controls and an upregulation of s100␤ is accompanied by enhanced mucosal NO levels similar to mucosa from Crohn patients (10,57). EGC share more similarities with astrocytes in the central nervous system than with Schwann cells of the peripheral nervous system (15,29).…”
Section: Effects Of Enteric Glial Cells On Intestinal Epithelial Barrmentioning
confidence: 99%
“…It has been proposed that the gliaspecific protein S100β is a pro-inflammatory mediator acting via the receptor for advanced-glycation end products) to increase production of NO in the mucosa (84,85). Furthermore, upon bacterial stimulation, EGCs upregulate expression of MHC class II, which suggests that they actively respond to the colonization of the gut lumen by microbiota and participate in antigen presentation to the adaptive immune system (86). In adult mice, lineage-tracing experiments under conditions of acute neuronal loss after chemical injury demonstrated that EGCs have the capacity to transdifferentiate into neurons in vivo.…”
Section: Microbiota Influence On Ens Developmentmentioning
confidence: 99%